Spectrophotometric method for detecting lead (II) ions using a chemosensor of the thiosemicarbazone-linked phenyl sulphone moiety - Gharam I. Mohammed; Sulafa Nassar; Thoraya A. Farghaly (Results in Chemistry)
For the spectrophotometric determination of lead, a novel, straightforward, and sensitive technique has been described. In an alkaline media (pH 12), lead)II (forms a yellow chelate with 2-(1-(4-methoxyphenyl)-2-(phenylsulfonyl)ethylidene)-hydrazine-1-carbothioamide. The complex's molar absorptivity at 257 nm (λmax) is 1.6 × 103 L mol−1 cm−1, and its quantification and detection limits are 3.04 μg mL−1 (15 μmol L−1) and 1.25 μg mL−1 (6.03 μmol L−1), respectively. In the concentration range of (2.4–12) × 10−5 mol L−1, Beer's law is followed. The technique has also been used for Pb recovery investigations in water samples. The molar ratio, which was 1:1 (L: Pb2+), guaranteed that a metal complex would form between the L and Pb ions. Simple, inexpensive, easy to use, rapid detection, and sensitivity are only a few advantages of the employed technique. The isolation and study of the solid complex (L-Pb) has provided more insight into the structure and stoichiometry of the complex that forms in solution between Pb(II) and L ligand. By using analytical methods such elemental analysis, spectral mass, UV–Vis spectra, and thermal analysis, the structure of the solid complex has been clarified.